Uji Validitas dan Reliabilitas Instrumen Penelitian Tingkat Pengetahuan dan Sikap Mahasiswa terhadap Pemilihan Suplemen Kesehatan dalam Menghadapi Covid-19 - Heny Puspasari; Weni Puspita (Jurnal Kesehatan, 2022)
Research instruments that can be accepted in a study must comply with standards that have been through data validation and reliability tests. The validation test can use the Pearson Product Moment formula and test using the t-test and see the interpretation of the correlation index with the total score. Reliability measurements can be used Cronbach's alpha value method. The purpose of this study was to test the validity and reliability of the questionnaire in researching the level of knowledge and attitudes of students towards the selection of health supplements in the face of Covid-19. This research was conducted with a qualitative analysis research design with an analysis unit of active female students at the Akademi Farmasi Yarsi Pontianak. Prospective data collection for active students at all levels/semesters by administering a questionnaire containing ten indicators of knowledge about Covid-19 and attitudes towards consuming health supplements. The questionnaire was valid and reliable with a correlation value (Pearson Correlation) for indicators of knowledge and attitudes r-value 0.5-0.8 than r table 0.3 and Cronbach's alpha value of knowledge 0.5 and attitudes 0.9. Based on the results of the discussion, it can be concluded that the questionnaire can be declared valid and reliable.